Teachers' construction of the constructivism approach in social studies learning at Semarang Junior High School - Manurung, Nadya Tridrisna; Atmaja, Hamdan Tri; Priyanto, Agustinus Sugeng (Universitas Negeri Semarang, 2024)
In Indonesian education, there has been a crisis of learning and a stagnation, combined with social studies teachers' incapacity to contextualize, apply, and meaningfully make relevant social studies instruction available to students. The Ministry of Education, Culture, Research, and Technology is reviving learning in this regard through the Independent Curriculum, which has a foundation in constructivism. This study aims to identify and explain the social construction, planning and implementation of social studies teachers in using a constructivism approach to social studies learning. This study uses qualitative methods. The result is that the social construction of teachers at SMPN 3 and 39 Semarang City is progressing well, but there is still room for improvement. This is evident in the poorly planned and executed social studies curriculum that uses a constructivism approach. Therefore, there are variations in the design and execution of the constructivism method in the classes taught by the two instructors, even though the social studies teachers' building of the approach in both schools is suitable and competent.